Legal Basis for the Development of Social Capital in the Conditions of the State Transition to an Innovative Economy. / Base jurídica para el desarrollo del Capital Social en las condiciones de la Transición del Estado a una Economía Innovadora - Abramov, Ruslan A.; Morozov, Ivan V.; Sokolov, Maksim S. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT The Union state-the Union of Russia and Belarus – is the most significant integration project in the CIS space, which marked the change of centrifugal tendencies in the post-Soviet space by centripetal ones. Russia and Belarus were among the first CIS member States to realize the need for close integration. Almost immediately after the collapse of the Soviet Union, Russia and Belarus signed bilateral trade and economic agreements, which recognized the right of the parties to pursue an independent foreign economic policy. Thus, Russia and Belarus were the pioneers of integration processes in the region.RESUMEN El estado de la Unión - la Unión de Rusia y Belarús - es el proyecto de integración más importante en el espacio de la CEI, que marcó el cambio de las tendencias centrífugas en el espacio postsoviético por las centrípetas. Rusia y Belarús fueron los primeros miembros de los estados de CEI en darse cuenta de la necesidad de una estrecha integración. Casi inmediatamente después del colapso de la Unión Soviética, Rusia y Bielorrusia firmaron acuerdos comerciales y económicos bilaterales, que reconocían el derecho de las partes a perseguir una política económica extranjera independiente. Así, Rusia y Belarús fueron los pioneros de los procesos de integración en la región.